Children environmental exposure to particulate matter and polycyclic aromatic hydrocarbons and biomonitoring in school environments: A review on indoor and outdoor exposure levels, major sources and health impacts. (March 2019) - Oliveira, Marta; Slezakova, Klara; Delerue-Matos, Cristina; Pereira, Maria Carmo; Morais, Simone
Abstract: Children, an important vulnerable group, spend most of their time at schools (up to 10 h per day, mostly indoors) and the respective air quality may significantly impact on children health. Thus, this work reviews the published studies on children biomonitoring and environmental exposure to particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) at school microenvironments (indoors and outdoors), major sources and potential health risks. A total of 28, 35, and 31% of the studies reported levels that exceeded the international outdoor ambient air guidelines for PM10, PM2.5, and benzo(a)pyrene, respectively. Indoor and outdoor concentrations of PM10 at European schools, the most characterized continent, ranged between 7.5 and 229 μg/m 3 and 21–166 μg/m 3, respectively; levels of PM2.5 varied between 4 and 100 μg/m 3 indoors and 6.1–115 μg/m 3 outdoors. Despite scarce information in some geographical regions (America, Oceania and Africa), the collected data clearly show that Asian children are exposed to the highest concentrations of PM and PAHs at school environments, which were associated with increased carcinogenic risks and with the highest values of urinary total monohydroxyl PAH metabolites (PAH biomarkers of exposure). Additionally, children attending schools in polluted urban and industrial areas are exposed to higher levels of PM and PAHs with increased concentrations of urinary PAH metabolites in comparison with children from rural areas. Strong evidences demonstrated associations between environmental exposure to PM and PAHs with several health outcomes, including increased risk of asthma, pulmonary infections, skin diseases, and allergies. Nevertheless, there is a scientific gap on studies that include the characterization of PM fine fraction and the levels of PAHs in the total air (particulate and gas phases) of indoor and outdoor air of school environments and the associated risks for the health of children. There is a clear need to improve indoor air quality in schools and to establish international guidelines for exposure limits in these environments. Highlights: Median PM10 and PM2.5 exceeded WHO guidelines indoors in European and Asian schools. Asian schools presented higher levels of PM and PAHs than European and American ones. Scarce information exists on PAH levels in the fine PM fractions and gas phase. Levels of PAH metabolites were increased in children from schools at polluted areas. Poor indoor air quality at schools promotes children cardio-respiratory illnesses.